Animal Welfare Standards and Australia's Live Exports Industry to Indonesia: Creating an Opportunity Out of a Crisis - Marie T. Hastreiter (Washington University Global Studies Law Review, 2013)
This Note will explore whether Australia can remain a leader in the adoption of animal welfare standards while also preserving the viability of Australian farmers’ jobs and livelihoods. Part II analyzes the history of the Australian live exports industry and outlines current industry standards and regulations. Parts III and IV discuss New Zealand’s live exports industry and how New Zealand’s model would work for Australia. Part V analyzes the impact that Brazil’s industry could have on Australia, why Australia should implement a live exports policy like New Zealand’s and how to accomplish this, and the positive economic impact a ban on the live exports industry would have on Australia’s agriculture industry. This Note concludes by encouraging the Australian government to use the recent live exports industry crisis as an impetus for policy change. The Australian government can simultaneously implement an agricultural policy that reflects its stringent animal welfare standards and protects the livelihood of Australian farmers. The Australian government can accomplish this balance by passing legislation that would ban the live exports industry in progressive stages, giving farmers and export markets time to adjust to the ban, and by developing new markets, industries, and substitute exports.
Keywords: animal welfare; Australia; Indonesia; live exports industry; animal welfare standards; New Zealand